A dengue vaccine whirlwind update - Ruwandi Kariyawasam; Mark Lachman; Saniya Mansuri; Sumontra Chakrabarti; Andrea K. Boggild (Therapeutic Advances in Infectious Disease, 2023)
Dengue virus (DENV) is a mosquito-borne single-stranded RNA virus of the Flaviviridae family with four serotypes (DENV1, DENV2, DENV3, and DENV4) circulating many tropical and subtropical regions of the world. Endemic in more than 100 countries, DENV results in over 400 million cases annually, a subset presenting with severe or life-threatening illnesses such as dengue hemorrhagic fever (DHF) or dengue shock syndrome (DSS). While no specific treatments outside of supportive management exist, vaccines are an area of major research with two vaccines, Dengvaxia ® (CYD-TDV) and Denvax ® (TAK003), recently licensed for clinical use. CYD-TDV is highly efficacious in children 9 years or older who have had prior DENV infection due to the high risk of severe disease in seronegative children aged 2–5 years. Meanwhile, TAK003 has shown efficacy at 97.7% and 73.7% against, DENV2 and DENV1, respectively, in phase 3 clinical trials across Latin America and Asia in healthy children aged 4–16 with virologically confirmed dengue. Other vaccines including TV003 and TV005 continue to be developed across the world, with the hopes of entering clinical trials in the near future. We discuss the current state of vaccine development against dengue, with a focus on CYD-TDV and TAK003 as promising novel vaccines to target this neglected tropical disease (NTD).